The bank-specific and macroeconomic determinants of bank profitability in Indonesia - Xie, Jianan (2017)
The purpose of this paper is to explore the influences of internal factors and macroeconomic determinants of bank performance in Indonesian banking sector during the period from 2011 to 2016. By using an unbalanced panel data of 136 banks in Indonesia banking sector, a fixed effect model is used to capture the unobserved heterogeneity of banks. With ROAA and ROAE as two performance measure to capture the difference in determinants of Indonesian banking, loan divided by total assets, loan loss reserves over total loans, liquid assets to total assets, loan to deposit and short-term funding, loan loss provisions to total loans, cost to income ratio, equity to total assets and bank size are selected as internal variables to represents asset quality, liquidity, credit risk, operating efficiency and capital adequacy of the banks. The GDP growth rate, concentration, MACPASS and unemployment rate used as external variables. The estimation results report that COSTI and LLPTL have a statistically significant and negative relationship with bank performance while LODEP is positive and significant related to Indonesian banking sector. However, the empirical results illustrate that all external variables are insignificant, which means that the correlation between external factors and Indonesia banking cannot be confirmed during the research period.